The Greek sovereign debt: Are there really any options? - Gregory T. Papanikos (Romanian Journal of Fiscal Policy (RJFP), 2014)
Debt Overhang is a controversial issue in the eurozone countries and is considered as one of the factors which created the current economic crisis. How to deal with sovereign debt has been debated both at the theoretical and policy making level. This paper looks at the Greek debt and four options are discussed: (a) unilateral default (b) unilaterally imposed austerity measures (c) restructuring through negotiating and (d) a tax on wealth to pay for the debt. Optimal options depend on the borrowing rate, debt maturity and debt haircut.
Keywords: H63; E62; H26; H21; 330; eurozone; debt; Greece